(untitled) (American Journal of Society and Law, 2025)
The emergence of Artificial Intelligence (AI) has given rise to unprecedented and momentous consequences across humanity. There is no doubt that AI, most especially, Generative (Gen) AI portents massive consequences within the entertainment industry. This article attempts to contribute to the overall discuss of gen AI within the entertainment industry, and covers the proper understanding of gen AI and how AI models are trained; the entertainment industry; the impact of gen AI on the entertainment industry globally; the advantages and disadvantages of deploying gen AI within the entertainment industry; and the legal tools available to manage the existential threat of gen AI to the entertainment industry. Therefore, the article explains and discusses AI broadly, gen AI specifically, the training process, the current developments within the entertainment industry regarding the adoption of AI, and the legal consequences of gen AI, such as, copyright infringements. This article concludes by emphasizing the quantum advantage of deploying gen AI as an effective tool within the entertainment industry, which shifts the focus from the threats gen AI portends for the industry at large, to its huge benefits if properly harnessed.